WHO IS THE SUBJECT OF HUMAN RIGHTS? DISCUSSION BETWEEN MARXISM AND POSTFUNDACIONALISM - Herrera Rodríguez, Omar Santiago (2017)
The present article examines the answers provided by Karl Marx and postfundacionalist theory about the problem of who is the subject of human rights, with the objective to develop a marxist reading that allows defend human right, at the same time critizing the “politicista” reading of postfundacionalist theory.